The Impact of the EU Cohesion Policy Programmes on Polish Regions - Cieślik, Andrzej; Rokicki, Bartłomiej (Publishing House of the Wrocław University of Economics, 2009)
The aim of this paper is to assess the impact of the Community Support Framework (CSF) 2004-2006 on regional output and employment in Poland. We found that the ECP programmes will hardly affect economic performance of the most developed Polish voivodeships, at least directly, while the regions with medium and low level of per capita income may increase their economic growth. However, it is necessary to emphasize that our simulation results are valid in short term only and have been obtained under unrealistic assumption that all projects are accomplished in the same year. Therefore, future studies should take into account the long term impact of structural policies and allow for crowding-out and crowding-in effects of public spending on private investment or capital depreciation. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 89-97